Differential Roles of Insulin Receptor Substrates in Brown Adipocyte Differentiation - Tseng, Yu-Hua (American Society for Microbiology, 2004)
Insulin promotes adipocyte differentiation via a complex signaling network involving multiple insulin receptor substrates (IRSs). In cultured brown preadipocytes, expression of IRS-1 and IRS-2 mRNAs and proteins was at relatively high levels before and after differentiation into mature fat cells, while IRS-3 transcript was not detectable in preadipocytes but increased during the course of differentiation, and IRS-4 mRNA was barely detected in both states. To determine more precisely the roles of various IRS proteins in adipogenesis, we established and characterized brown preadipocyte cell lines from wild-type and IRS knockout (KO) animals. While wild-type, IRS-2 KO, and IRS-4 KO cells fully differentiated into mature adipocytes, IRS-3 KO cells showed a moderate defect in differentiation and IRS-1 KO cells exhibited a severe defect in the process. Cells lacking both IRS-1 and IRS-3 completely failed to differentiate. Expression of the adipogenic markers peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT/enhancer-binding protein alpha, fatty acid synthase, glucose transporter 4, and the transcription factor signal transducer and activator of transcription 5, as well as the brown-fat-specific markers PPARγ coactivator 1 alpha and uncoupling protein 1, mirrored the differentiation pattern. Reconstitution of the IRS-1 KO cells with IRS-1 and IRS-4, but not IRS-2 or IRS-3, compensated for the lack of differentiation in IRS-1 KO cells. A chimeric molecule containing the N terminus of IRS-1 and the C terminus of IRS-2, but not one with the N terminus of IRS-2 and the C terminus of IRS-1, also rescued differentiation. Expression of Wnt 10a, a molecule known to inhibit adipogenesis, was dramatically increased in the IRS-1 KO cells, and this could be reduced by overexpression of IRS-1 or IRS-4, which was correlated with restoration of differentiation. These data indicate that both IRS-1 and -3 play important roles in the differentiation of brown adipocytes and that the N terminus of IRS-1 is more important for this function of the molecule. Although IRS-4 is not essential for the process, overexpression of IRS-4 can compensate for the deficiency in differentiation in IRS-1 KO cells.